Diagnostic Assessment of the Development Potential of Regional Economies Using the Example of the Southern Federal District - E. Demyanenko , Andrei (International Journal of Psychosocial Rehabilitation, 2020)
The present study gives a diagnostic assessment of the development potential of the patterns, specifics and trends of regional economies in terms of their socio-economic status and development. The per capita income of the population, which are traditionally used in economic studies, do not properly reflect the true situation. The median income seems to be more appropriate to determine the per capita income of the population, since it reveals how much money a person receives in the middle of the lowest-to-highest income range for this or that section of the population. The ratio between the average per capita income and the minimum subsistence level is usually used to determine the population’s standard of living. In order to compare the population’s interregional purchasing power, statistics uses the value of a fixed set of consumer goods and services, determined on the basis of common consumption levels with average prices throughout the members of the Russian Federation. This study detected corresponding differences in the ratio between the median income and the fixed set of goods and services. It is this income which best reflects the minimum standard of living, and it is to be used as the subsistence minimum. The diagnostic assessment of the development potential of regional economies comprised the following key indicators: consumer investment portfolio of the regions’ potential development; organizational and technological processing in which raw products or goods-in-process are processed the second time and so on; living labor productivity in regions and in small businesses; potential in natural resources and regional taxes.